Protestant Ethic and Status-Attainment - Cohen, Jere (Sociological analysis, 1985)
The relationship between religion, the work ethic and socioeconomic success was examined using longitudinal survey data. High school studentsr designation of intrinsic work satisfaction as their prime criterion in job choice was related, though not strongly related, to religious affiliation and to strength of Protestant commitment. The stronger the emphasis on intrinsic work satisfaction, the higher a student's grade point average; higher grades led, in turn, to greater educational and occupational attainment.